MARKETING STRATEGY FOR FUTURE SAVINGS PRODUCTS: SHARIA MARKETING PERSPECTIVE - Trihudiyatmanto, M.; Novitasari, Ika; Kaukab, M. Elfan; Musfiroh, Mila Fursiana Salma; Nurhayati, Eni Candra; Hinawati, Titik (Jurnal ’Ulwan, 2024)
Competition between financial institutions in competing for third party funds has spurred them to innovate marketing strategies to attract customers in various ways. Marketing strategy is the steps taken to make decisions carefully in order to achieve the aims and objectives to be achieved by paying attention to the conditions of the surrounding environment. Sharia marketing is a marketing strategy that is permitted by ulama, because in concept and practice it does not conflict with sharia principles. The purpose of this research is to find out the marketing strategy for future savings products at KSPPS Marhamah and to find out the analysis of KSPPS Marhamah’s marketing strategy from a sharia marketing perspective. This type of field research uses qualitative methods. Data collection through interviews and documentation. After the data was collected, the validity of the data was tested using source triangulation and then subjected to qualitative descriptive analysis using the Miles Huberman model. The results of the research show that the marketing strategy carried out at KSPPS Marhamah in marketing future savings products uses a marketing mix which includes a product strategy that is needed by the community, a price strategy that prioritizes affordable prices, a location strategy that is easily recognized by potential members, and a promotional strategy to attract interest. member. The marketing strategy carried out by KSPPS Marhamah has implemented sharia marketing. The implication of this research is as reference material for leaders of Islamic financial institutions to implement appropriate strategies in running their businesses to be able to compete and continue to survive.